Derivative Semantics of Numerical Substantives (First Russian Decade) - Czerwiński, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2025)
This article examines formations such as двойка, тройка, десятка, двойня, тройня, четверня, пятерня, etc., with different suffixes. The author’s analysis involves both current and older or outdated material. The latter is derived from the dictionary of V.I. Dahl. The purpose of such a presentation has been to create a perspective from which to discover nominative and semantic mechanisms operating in the selected group of words, and to address their internal linguistic potential. The author is concerned with the frequency character of various formations and their stylistic features, and places particular emphasis on the outdated material, as it separates itself from the typical usage of modern words. The declared internal potential may reveal the features of new formations that are hidden in the language and do not always manifest themselves. The analysis involves three steps: Initially, the observed formations from единица to десятка are taken sequentially (structural form Rits(a) / Rk(a)), then formations such as двойня, тройня, четверня, пятерня (Rn'(a)), and finally, the remaining ones organized into structural groups with common suffixes. The article concludes by showing what unites such divisions, what distinguishes them, and how various nominative and semantic positions can be determined. Such a perspective opens up the possibility of further, more complete and more detailed analysis and involves referral to a more complete set of numerical substantives, including the formations that follow the first ten quantitative and ordinal units.